Debt or equity? Financial impacts of R&D support across firm demographics - Moon, Byunggeor (Technological and Economic Development of Economy, 2025)
This study utilizes data from Korea’s Research and Development (R&D) grant program to examine the impact of receiving an R&D grant on a firm’s ability to obtain external financing, taking into account the heterogeneous effects based on firm size and characteristics. By employing the propensity score matching method, we establish the causal effect of R&D support on financing and discover that R&D grants have differential effects on debt and equity financing. Our findings indicate that larger firms are more likely to acquire subsequent debt financing, whereas small firms that receive R&D grants exhibit an increased likelihood of securing equity financing, particularly among young firms. Furthermore, we identify a certification effect of R&D grants, implying that such grants may serve as indicators of the potential success of small, young firms in the market. Collectively, this study illuminates the role of R&D grants in firms’ financing decisions, providing valuable insights for policymakers and firms seeking to secure external financing. First published online 12 December 2024